ALIRAN PEMIKIRAN USHUL FIQH DAN PENGARUHNYA TERHADAP PENDEKATAN HUKUM ISLAM - Hanif Aidhil Alwana (Institut Agama Islam Negeri Batusangkar, 2020)
Law is the result of Fuqaha's ijtihad regarding an act of mukallaf, in its understanding Islamic law is derived from the al-Quran and Sunnah. Although the existence of the al-Qur`an and the Sunnah is not in doubt, the understanding of law from these sources often experiences ikhtilaf (differences) of opinion, besides this the risk of causing divisions in society, these problems are influenced by schools of legal thought. This paper will describe the history of these schools of thought and their relevance in establishing law. The method used was descriptive analysis, with a qualitative approach based on the content (content analysis) of previous writings. In this paper, it is found that the difference in legal opinion is influenced by the way of thinking of the mujtahid which is divided into mutakallimin schools which are identical to understanding the legal text; fuqaha with the style of rules and legal reasons extracted from the law-making text (syari`) or also termed a contextual style; and a combination that seeks to combine the two types of legal understanding, this gives birth to different legal features. This is the scientific treasure of Islamic law which must be developed in the future to always exist in answering legal problems in the future.